(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
This study examines the implementation of Community Based Contracting (CBC) in a school infrastructure revitalization program in Bangli Regency. It aims to evaluate how the self-managed construction scheme impacts financial optimization, social participation, and managerial dynamics. Using a qualitative descriptive approach with case studies of two different schools, the study highlights the application of Value Engineering (VE) principles through the Contract Change Order (CCO) instrument. It found that the CBC method provided significant budget flexibility without changing the final nominal value of the work. Overruns on structural and architectural items were successfully rationalized, allowing for the reallocation of funds amounting to 12.42% to 19% of the contract value. Beyond technical efficiency, the CBC approach can foster a sense of ownership among stakeholders through their participation in design decision making and stimulate the local economy by leveraging local labor and material supply chains. However, the study found operational challenges, particularly the excessive workload experienced by teachers due to their dual roles as educators and project managers, in addition to the complexity of construction tax administration. Ultimately, this study concludes that although CBC is highly effective for holistic budget and facility optimization, further intensive technical and administrative assistance is needed to ensure that the primary tasks of educators in schools are not disrupted.